Compliance of atrial fibrillation treatment with the ABC pathway in patients with concomitant diabetes mellitus in the Middle East based on the Gulf SAFE registry. (25th November 2020) - Domek, M.G; Gumprecht, J.J; Li, Y.G; Rashed, W; Al Qudaimi, A; Amin, H; Gumprecht, J.M; Lip, G.Y.H
Abstract: Introduction: Atrial fibrillation (AF) and diabetes mellitus (DM) constitute a heavy burden on healthcare expenditure due to their negative impact on clinical outcomes in patients. DM is highly prevalent in the Middle East. The Atrial fibrillation Better Care (ABC) pathway provides a simple step-by-step strategy with an integrated, holistic approach to AF management: A, Avoid stroke (Anticoagulation); B, Better symptom management; C, Cardiovascular and comorbidity risk management. Aim: Evaluation of the AF treatment compliance to ABC pathway regimen in patients with DM based on a large real-world registry from the Middle East region. We assessed the impact of ABC-pathway compliance on all-cause mortality and the composite outcome of stroke or systemic embolism, all-cause death and cardiovascular hospitalizations. Methods: From 2043 patients in the Gulf SAFE registry, 603 patients with DM were included in an analysis of compliance with components of the ABC pathway: A, oral anticoagulation (OAC) use in patients with CHA2DS2-VASc score ≥1 (≥2 in females); B, AF symptoms according to the European Heart Rhythm Association (EHRA) score; C, Optimized management of cardiovascular comorbidities e.g. blood pressure control, statins for vascular disease, etc. Results: From 606 patients, 86 (14.3%) patients were treated in compliance with the ABC pathway. During 1-year follow-up, 207 composite outcome events and 87 deaths occurred. Mortality was significantly lower in the ABC-adherent group vs non-ABC compliant (5.8% vs 15.9%, p=0.0014, respectively) (Figure). On multivariate analysis, ABC-adherent management was associated with a lower risk of all-cause death and the composite outcome after 6 months (OR 0.18; 95% CI, 0.42–0.75 and OR 0.54; 95% Cl, 0.30–1.00, respectively) and at 1 year (OR 0.30; 95% Cl, 0.11–0.76 and OR 0.57; 95% Cl, 0.33–0.97, respectively) vs the non-ABC group (Table). Conclusions: Integrated AF care, according to ABC pathway, was independently associated with a lower risk of all-cause death and the composite outcome, in DM patients with AF. This highlights the importance of a comprehensive and holistic approach to AF management. Funding Acknowledgement: Type of funding source: None